Diffuse exanthematous drug eruption associated with intravenous immunoglobulin. Issue 1 (2nd January 2021) - Paudel, Anish; Basnet, Sijan; Tharu, Biswaraj; Bohra, Nidrit
Abstract: Diffuse exanthematous drug eruption due to intravenous immunoglobulin (IVIg) is a rare adverse event reported only in case reports. We present a case of a 71-year-old woman with a diffuse maculopapular rash 5 days after receiving an IVIg infusion for treatment of chronic inflammatory demyelinating polyneuropathy. She was managed conservatively with antihistamines; she was already receiving prednisone 25 mg daily as part of treatment for the neuropathy. The rash resolved over 2 weeks.